Posttreatment Effects of Topiramate Treatment for Heavy Drinking. (December 2014) - Kranzler, Henry R.; Wetherill, Reagan; Feinn, Richard; Pond, Timothy; Gelernter, Joel; Covault, Jonathan
<x xml:space="preserve">Abstract</x> Background We examined whether the effects of topiramate and a single nucleotide polymorphism (rs2832407) in GRIK1, which encodes a kainate receptor subunit, persisted following a 12‐week, placebo‐controlled trial in 138 heavy drinkers with a treatment goal of reduced drinking. During treatment, topiramate 200 mg/d significantly reduced heavy drinking days and increased the frequency of abstinent days (Am J Psychiatry, 2014, 171:445). In the European‐American (EA) subsample (n = 122), rs2832407 moderated the treatment effect on heavy drinking. Methods Patients were re‐interviewed 3 and 6 months after the end of treatment. During treatment, we obtained 92.4% of drinking data, with 89.1 and 85.5% complete data at the 3‐ and 6‐month follow‐up visits, respectively. We examined 4 outcomes over time in the overall sample and the EA subsample: percent heavy drinking days (PHDD), percent days abstinent (PDA), serum γ‐glutamyl transpeptidase (GGTP) concentration, and a measure of alcohol‐related problems. Results In the full sample, the lower PHDD and higher PDA seen with topiramate treatment were no longer significant during follow‐up. Nonetheless, the topiramate‐treated patients had lower alcohol‐related problem scores during treatment and both follow‐up periods. Further, in the EA subsample, the greater reduction in PHDD seen with topiramate treatment in rs2832407*C‐allele homozygotes persisted throughout follow‐up, with no significant effects in A‐allele carriers. A reduction in GGTP concentration was consistent with the reduction in heavy drinking, but did not reach statistical significance. Conclusions There are persistent therapeutic effects of topiramate in heavy drinkers, principally in rs2832407*C‐allele homozygotes.